Feed Forward Equalization Simulation Model for High-Speed Channel Applications - Castro-Artavia, Rebeca (Instituto Tecnológico de Costa Rica, 2016)
This thesis describes the development of simulation models of FFE stages (Feed Forward Equalizer) in transmitters for high-speed channel analysis. The implementation of this equalizer was performed using two different tools: ADS (Advance Design System) by Keysight, which is a commercial tool and SPITDS (Signal and Power Integrity Time Domain Simulator), which is a simulator developed by the Institute of Electromagnetic Theory at the Technical University of Hamburg in Germany. Additionally, the LMS (Least Mean Square) algorithm was implemented in MATLAB and ADS to adjust the equalizer coefficients, in order to have a better signal recovery. Different channels were designed to make comparisons and verify the performance of different implementations of FFE with LMS. Both implementations of the Feed Forward Equalizer and LMS algorithm worked properly, which allows the application of the equalization FFE and the calculation of the equalizer coefficients for signal integrity analysis.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Ecualizador; Algoritmos; Simuladores; Señales; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering